Reconstruction of Ethics Supervision System Towards Constitutional Court Justice - Wiryanto Wiryanto; Moch Bakri; Masruchin Ruba’i; Prija Djatmika (The Constitutional Court of the Republic of Indonesia, 2017)
Ethics supervision of constitutional justices is an important issue for the development of ethics supervision system in the Constitutional Court, because the supervision of constitutional justices is a means of maintaining the independence and impartiality of constitutional justices, which is in fact the main pillar of an independent judiciary. In its development, there has always been a debate about the ethics supervision of the constitutional justices, whether the justices should be overseen externally or internally. This is because, juridically, the law does not regulate it clearly. Based on the above background, the research issues drawn are: (1) What is the significance of ethics supervision toward constitutional justices ?; (2) What is the system of ethics supervision of constitutional justices according to Indonesia’s current positive law, (3) How to reconstruct the system of ethics supervision of constitutional justices more optimally in the future? Based on the result of the research entitled “Reconstruction of Ethics Supervision System toward Constitutional Justice”, the following conclusions are obtained: (1) Based on philosophical, juridical and empirical perspective, ethics supervision of constitutional justices has important meaning in order to maintain and uphold the honor, dignity, and the behavior of constitutional justices. (2) Based on the analysis of the evolution of the ethics supervision system, the result shows that the ethics supervision system toward constitutional justices which is always changing indicates that there is still no standard system as a guideline for the enforcement of alleged violation of ethics against the constitutional justices. Therefore, there is a need for normative reconstruction of the ethics supervision system toward constitutional justices through legislation. (3) The reconstruction of the ethics supervision system toward constitutional justices can be done through: a. Amendment to the 1945 Constitution by adding a new norm governing the provision on ethics supervision system toward constitutional justices, b. Amendment to the Constitutional Court Law.